Instructional technology and media for learning - Smaldino, Sharon E.; Lowther, Deborah L.; Russell, James D. (Pearson Education, 2012)
This edition renowned text places readers squarely in the classroom while providing a framework that teaches them to apply what they learn about computers, multimedia, Internet, distance learning, and audio/visual technologies to the 21st Century classroom instruction.